2012
DOI: 10.1111/j.1751-1097.2012.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Survey of Substituted Indoles Reveals Consequences of a Stabilized 1Lb Transition

Abstract: Although tryptophan is a natural probe of protein structure, interpretation of its fluorescence emission spectrum is complicated by the presence of two electronic transitions, 1La and 1Lb. Theoretical calculations show that a point charge adjacent to either ring of the indole can shift the emission maximum. This study explores the effect of pyrrole and benzyl ring substitutions on the transitions’ energy via absorption and fluorescence spectroscopy, and anisotropy and lifetime measurements. The survey of indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
7
16
0
Order By: Relevance
“…Therefore, we give strong theoretical evidence for level inversion between the L a and L b states in indole derivatives and we outline the underlying mechanism for the process. Our results are discussed in view of recent experimental work [12] and we find good agreement between the two.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore, we give strong theoretical evidence for level inversion between the L a and L b states in indole derivatives and we outline the underlying mechanism for the process. Our results are discussed in view of recent experimental work [12] and we find good agreement between the two.…”
Section: Introductionsupporting
confidence: 84%
“…Moreover, while the lowest emitting state is the L a state at its optimized geometry when ADC(2)/cc-pVDZ is used, the lowest emitting state is L b at its optimized geometry when ADC(3)/cc-pVDZ is used. The experimental fluorescence emission energy of indole vapor is 4.20 eV [12] and this is in excellent agreement with the 4.42 eV value calculated for the L b state at its equilibrium geometry using ADC(3)/cc-pVDZ. Considering the theoretical results for indole in the gas phase both for absorption and emission, it is found that ADC(2)/cc-pVDZ gives consistently higher energies for the L a state by about 0.2-0.3 eV, which is taken into account in the interpretation of the results to follow.…”
Section: Bondsupporting
confidence: 72%
See 3 more Smart Citations